Multiplex PCR for bacterial, viral and protozoal pathogens in persistent diarrhoea or persistent abdominal pain in Côte d’Ivoire, Mali and Nepal - Jasuja, Jasmin Kaur; Bub, Florian; Veit, Jonas; Fofana, Hassan K. M.; Sacko, Moussa; Saye, Rénion; Chatigre, Justin K.; N’Goran, Eliézer K.; Yao, Joel A.; Khanal, Basudha; Koirala, Kanika; Bhattarai, Narayan R.; et al. (Scientific reports, 2024)
In contrast to acute diarrhoea, the aetiology of persistent digestive disorders (≥ 14 days) is poorly understood in low-resource settings and conventional diagnostic approaches lack accuracy. In this multi-country study, we compared multiplex real-time PCR for enteric bacterial, parasitic and viral pathogens in stool samples from symptomatic patients and matched asymptomatic controls in Côte d’Ivoire, Mali and Nepal. Among 1826 stool samples, the prevalence of most pathogens was highest in Mali, being up to threefold higher than in Côte d’Ivoire and up to tenfold higher than in Nepal. In all settings, the most prevalent bacteria were EAEC (13.0-39.9%) and Campylobacter spp. (3.9-35.3%). Giardia intestinalis was the predominant intestinal protozoon (2.9-20.5%), and adenovirus 40/41 was the most frequently observed viral pathogen (6.3-25.1%). Significantly different prevalences between symptomatic and asymptomatic individuals were observed for Campylobacter, EIEC and ETEC in the two African sites, and for norovirus in Nepal. Multiple species pathogen infection was common in Côte d’Ivoire and Mali, but rarely found in Nepal. We observed that molecular testing detected multiple enteric pathogens and showed low discriminatory accuracy to distinguish between symptomatic and asymptomatic individuals. Yet, multiplex PCR allowed for direct comparison between different countries and revealed considerable setting-specificity.
Gesehen am 29.11.2024